From Local Wisdom to Classroom Practice: The Transformation of Gorontalo Oral Literature in Language Teaching Management at Madrasah was carried out.: Dari Kebijaksanaan Lokal ke Praktik di Kelas: Transformasi Sastra Lisan Gorontalo dalam Pengelolaan Pengajaran Bahasa di Madrasah telah dilaksanakan. - Umar, Yusuf; Pateda, Lamsike; Hula, Ibnu Rawandhy N.; Mariana, Ana (ELOQUENCE : Journal of Foreign Language, 2024)
Background: Islamic education in madrasahs is often disconnected from local cultural contexts, rendering Islamic values emotionally and culturally irrelevant to students. In Gorontalo, oral literary forms such as tuja’i, taleningo, and tinilo embody Islamic values aligned with the principle of rahmatan lil-‘alamin (mercy for all creation); however, their integration into language teaching practices remains sporadic and unsystematic. Purpose: This study aims to (1) identify Gorontalo oral literary forms relevant to language instruction in madrasahs, (2) analyse strategies for their transformation into classroom practices, and (3) formulate a localised, wisdom-based language teaching management model. Method: The study employs an exploratory-descriptive qualitative approach with a multi-site case study design across three regencies in Gorontalo. Data were collected through in-depth interviews, participant observation, and documentation involving 12 teachers, 6 madrasah principals, 8 local cultural leaders, and 24 students. Data analysis followed the model proposed by Miles, Huberman, and Saldaña (2020), guided by grounded theory principles. Results and Discussion: indicate that tuja’i, taleningo, and tinilo hold the greatest potential as authentic instructional materials due to their embedded values of tauhid (monotheism), moral character (akhlak), and social responsibility. Effective classroom strategies include performative learning approaches—such as declamation, tanggomo-based dialogues, and collaborative projects—which significantly enhanced students’ speaking fluency, linguistic politeness, and cultural pride (reported by 83% of students). Nevertheless, major barriers are managerial in nature: a complete lack of teacher training (reported by 100% of respondents), absence of written teaching modules, the dominance of the national curriculum, and insufficient digital documentation. The integration of oral literature extends the theoretical frameworks of Communicative Language Teaching and Funds of Knowledge into the context of localised Islamic education. Conclusions and Implications: Gorontalo oral literature constitutes a strategic pedagogical resource that strengthens linguistic competence, Islamic character, and cultural identity. This research recommends enhancing teacher professional development, developing oral-literature-based teaching modules, and implementing policies supporting localised curriculum autonomy through structured partnerships between madrasahs and customary institutions to revitalise the Gorontalo language and foster sustainable Islamic education.